The maiden and her monster - Martinez, Maddie (Tor Publishing Group, 2025)
""A dark and endlessly enchanting fairy tale.... I adored every page."-#1 New York Times bestselling author Ava Reid The Maiden and Her Monster is a gorgeous, atmospheric debut fantasy rooted in history, folklore, and sapphic romance-perfect for fans of Katherine Arden, Ava Reid, Hannah Whitten, and Naomi Novik. The forest eats the girls who wander out after dark. As the healer's daughter, Malka has seen how the wood's curse has plagued her village, but the Ozmini Church only comes to collect its tithe, not to protect heretics with false stories of monsters in the trees. So when a clergy girl wanders too close to the forest and Malka's mother is accused of her murder, Malka strikes an impossible bargain with a zealot Ozmini priest. If she brings the monster out, he will spare her mother from execution. When she ventures into the shadowed woods, Malka finds a monster, though not the one she expects: an inscrutable, disgraced golem who agrees to implicate herself, but only if Malka helps her fulfill a promise first and free the imprisoned rabbi who created her. But a deal easily made is not easily kept. And as their bargain begins to unravel a much more sinister threat, protecting her people may force Malka to endanger the one person she left home to save-and face her growing feelings for the very creature she was taught to fear"-- Provided by publisher.